Estudo de algumas características ecofisiológicas na produção de mudas de Muntingia calabura L. em função de tipos de substratos e níveis de irradiância - Castro, Evaristo Mauro de (1995)
The present srudy was conducted under laboratory and nursery conditions at the Biology Department of the Universidade Federal de Lavras (UFLA), with the aim of studying different types of substrates and levels of irradiance upon the growth of calabura (Muntingia calabura L.) seedlings. This study was carried out in two sucessive phases: a) observe the best kind of substrate; b) evaluation of irradiation levels upon the growth of calabura seedlings. Four types of substrates were utilized [S, - subsoil material: vermiculita: cattle manure (40:40:20); S2 - vermiculite: cattle manure (80:20); S3 - subsoil material: cattle manure (80:20) and S4 -subsoil material], being the growing of the cuttings accomplished in tublets. The experimental design utilized was the completely randomized, with four replications, where each plot was made up of three plants each. The evaluations relative to height, stem diameter, weight of total dry matter, leaf, stem and root, leaf area, LAR and root/shoot ratio were undertaken at 130 days after sowing. The results obtained allowed to conclude that the S substrate was the one which afforded best development of the seedlings, taking into consideration the morphophysiological characteristics evaluated. At the second steps, the calabura seedlings of 130 days of age were subjected to three levels of irradiance (full sunlight, 30 and 50% of shading), corresponding to 100%, 67% and 48% of the active photosynthetic radiation (APR). A split plot experimental design in randomized blocks with three replications was used. Each replication made up of20 plants. The evaluations relative to the physiological indices of growth such as NAR, RGR, LAR, SLA, leaf area, height, stem diameter, dry matter weight of leaves, stem, and total, root/shoot ratio and partitioning of dry matter among the several organs were made at 5times with 10 days intervals. The evaluations of the clorophyl contents were performed at 40 days after induction of light treatments. The plants cultivated in 100% of APR full sunlight as compared with the ones grown under 67 and 48% of APR showed decreased total dry matter accumulation, decreased values of stem diameter, height and leaf area. However, the highest net assimilatory rates (NAR) and dry matter partitioning to roots were obtained in full sunlight grown-plants. Concerning the chlorophyll contents, trends to fall with increasing light intensity were observed, being the lowest values observed, on full sunlight - cultivated plants.